Impaired control of L-type voltage-dependent calcium channels in experimental hypertension - Kuneš, Jaroslav; Líšková, Silvia; Dobešová, Zdena; Behuliak, Michal; Zicha, Josef (Physiological research, 2009)
Blood pressure (BP) level results from the balance of vasoconstrictors (mainly sympathetic nervous system) and vasodilators (predominantly nitric oxide and endothelium-derived hyperpolarizing factor). Most of the forms of experimental hypertension are associated with sympathetic hyperactivity and endothelial dysfunction. It is evident that nitric oxide and norepinephrine are antagonists in the control of calcium influx through L-type voltage-dependent calcium channels (L-VDCC). Their effects on L-VDCC are mediated by cGMP and cAMP, respectively. Nevertheless, it remains to determine whether these cyclic nucleotides have direct effects on L-VDCC or they act through a modulation of calcium-activated K(+) and Cl(-) channels which influence membrane potential. Rats with genetic or salt hypertension are characterized by a relative (but not absolute) NO deficiency compared to the absolute enhancement of sympathetic vasoconstriction. This dysbalance of vasoconstrictor and vasodilator systems in hypertensive animals is reflected by greater calcium influx through L-VDCC susceptible to the inhibition by nifedipine. However, when the modulatory influence of cyclic nucleotides is largely attenuated by simultaneous ganglionic blockade and NO synthase inhibition, BP of spontaneously hypertensive rats remains still elevated compared to normotensive rats due to augmented nifedipine-sensitive BP component. It remains to determine why calcium influx through L-VDCC of hypertensive rats is augmented even in the absence of modulatory influence of major vasoactive systems (sympathetic nervous system, nitric oxide).
Keywords: vápníková signalizace; GTP-Binding Protein alpha Subunits, Gi-Go; financování organizované; Animals; hypertenze; nukleotidy cyklické; Sodium Chloride, Dietary; Sympathetic Nervous System; kuchyňská sůl; alfa-adrenergní receptory; vápníkové kanály - typ L; lidé; Calcium Channels, L-Type; proteiny vázající GTP - alfa-podjednotky Gi-Go; chloridové kanály; genetická predispozice k nemoci; vápník; Genetic Predisposition to Disease; Ion Channel Gating; krevní tlak; Financing, Organized; Nucleotides, Cyclic; gating iontového kanálu; Hypertension; sympatický nervový systém; Calcium; modely nemocí na zvířatech; Receptors, Adrenergic, alpha; Chloride Channels; Calcium Signaling; Disease Models, Animal; krysa rodu Rattus; potkani inbrední SHR; oxid dusnatý; zvířata; Blood Pressure; Rats; Rats, Inbred SHR; Nitric Oxide; Humans